Nutrition policy in Nigeria - Vanderkooy, A.; Verstraeten, Roosmarijn; Adeyemi, O.; Covic, Namukolo; Becquey, Elodie; Diatta, Ampa Dogui; Touré, Mariama (International Food Policy Research Institute, 2019)
This brief summarizes nutrition-relevant policies in Nigeria. We examine i) nutrition context, policy objectives, indicators, budget, and activities, ii) key beneficiaries, actors and coordination, iii) monitoring, evaluation, and accountability, and iv) whether current policies are aligned with the World Health Assembly (WHA) global targets.